Clinical considerations in the management of hidradenitis suppurativa in women - Emily K. Kozera, BMedS; Michelle A. Lowes, MBBS, PhD; Jennifer L. Hsiao, MD; John W. Frew, MBBS (Hons), MMed (Clin Epi), MS, FACD (International Journal of Women's Dermatology, 2021)
Hidradenitis suppurativa (HS) is a chronic, inflammatory disease of the skin with a predilection for women. The role of sex hormones, including estrogen and progesterone, is incompletely understood, but alterations in hormone levels may play a role in disease activity for many patients. Specific clinical considerations should be made for women with HS, particularly in the setting of pregnancy, childbirth, breastfeeding, and menopause. Current knowledge gaps regarding HS include the cumulative impact of disease across an individual's lifespan, as well as the mechanistic role of sex hormones in the disease. An improved understanding of the pathophysiologic role of hormones in HS would optimize our ability to use targeted therapies for hormonally driven disease. Psychological and psychosexual support for women with HS is an important facet of any holistic management strategy for the disease. This article integrates up-to-date pathogenic and mechanistic insights with evidence-based clinical management to optimize care for women with HS.